Design and application of discrete wavelet packet transform based multiresolution controller for liquid level system. (November 2017) - Paul, Rimi; Sengupta, Anindita
Abstract: A new controller based on discrete wavelet packet transform (DWPT) for liquid level system (LLS) has been presented here. This controller generates control signal using node coefficients of the error signal which interprets many implicit phenomena such as process dynamics, measurement noise and effect of external disturbances. Through simulation results on LLS problem, this controller is shown to perform faster than both the discrete wavelet transform based controller and conventional proportional integral controller. Also, it is more efficient in terms of its ability to provide better noise rejection. To overcome the wind up phenomenon by considering the saturation due to presence of actuator, anti-wind up technique is applied to the conventional PI controller and compared to the wavelet packet transform based controller. In this case also, packet controller is found better than the other ones. This similar work has been extended for analogous first order RC plant as well as second order plant also. Highlights: Discrete wavelet packet transform (DWPT) is used to develop multiresolution controller using NI Lab VIEW software. It can work faster compared to DWT based controller, conventional PI and Anti[HYPHEN]windup PI controller for LLS with time delay. Due to presence of sensor, performance of controllers has been compared in presence of noise also. Analogous RC plants (both first and second order) have been simulated and tested both in presence and absence of noises. NI Lab VIEW Identification toolbox is used to find out the transfer function of open loop system with different controllers. Stability of SISO system with PI controller and wavelet controller for second order system has also been studied.